Some explicit forrnulae for heteroclinic solutions to scalar second order ordinary differential equations - Kaźmierczak, B. (Archives of Mechanics, 1996)
We derive some explicit formulae for heteroclinic pairs for scalar ordinary differential equations of the form u" + vλ(u)u’ - su(u - a)(u - 1)(1 + ϕ(u)) = 0, where λ is an arbitrary polynomial in ϕ and is properly chosen. The results are used in a simple model of plasma sustained by a laser beam.